Quality criteria for evaluating creative and interactive science dissemination in public outreach efforts: A scoping review. - Priscilla Van Even; Bieke Zaman; Karin Hannes (PLoS ONE, 2025)
Creative and interactive science dissemination is gaining recognition as an important component of public science communication, particularly in efforts to bridge the gap between science and society. This scoping review aims to identify science-based quality criteria to develop a conceptual framework for evaluating the quality of public dissemination practices. The research question of this review is: What criteria are described and used in the literature to assess the quality of creative and interactive public science dissemination practices? We mapped, identified, and synthesized key criteria by conducting a scoping review in accordance with the Joanna Briggs Institute (JBI) guidelines. The review focused on studies from 2004 onwards, reflecting the growing role of digital platforms and the rise of social media in public science dissemination. An initial search retrieved 8745 studies from the ERIC (USDE), Web of Science (Clarivate), Scopus (Elsevier), ProQuest Central (ProQuest), Open Dissertations (EBSCO), and Communication and Mass Media Complete (EBSCO) databases. After a three-stage screening process by multiple, independent screeners, 18 studies were selected that met the inclusion criteria (perspective, outcome, phenomenon of interest, and study domain). The framework was developed through iterative thematic analysis. Its comprehensiveness, practical relevance, and applicability were further examined through face validity workshops with practitioners and academics. The resulting evaluation framework comprises three thematic sets of criteria: normative criteria (addressing the scientific base of the dissemination), substantive criteria (covering translation, presentation, and design of the science dissemination), and performative criteria (focusing on the impact of the dissemination). This framework is intended to support the development of science communication that is engaging, inclusive, and impactful for broad audiences, while also encouraging reflective practice among science communicators.